Od prožnosti do prekarnosti dela - Kanjuo-Mrčela, Aleksandra (Teorija in praksa, 2015)
Ten years ago the analysis of the situation on the labour market in Slovenia and in other countries notified the increasing flexibility of labour and employment and the need of flexicurity. Recent analyses suggest that changes in the last decade in many European countries, including Slovenia went in the opposite direction - fewer workers have the perspective of flexicurity, while for most, and especially the youth working lives are characterized by an increasing precariousness. This article has two purposes: to contribute to the current conceptual debate on the flexibility and precarity and to contribute to the understanding of the observed changes at the labour market in Slovenia.
Keywords: mladi; prekarno delo; prekarnost; prožnost; trg dela; varna prožnost; zaposlovanje